Karakteristik Mekanis Material Geokomposit Ringan Tanah – EPS Stabilisasi Fly Ash - Ichsan Rauf; Tri Harianto; Ardi Arsyad; Astiah Amir (Universitas Teuku Umar, 2021)
This laboratory experiment intended to develop lightweight embankment material in using fly ash as a stabilized agent on soft soil and the addition of expanded polystyrenes (EPS). The fly ash derived from combustion of palm shells and tea in drinks manufacture process. In order to analyze the performance of this material, compressive strength test were applied to several composition and treatment on each sample. The samples were prepared with composition of binding agent between 3%, 5%, 10% and 15% based on samples weight, meanwhile the addition of EPS with composition 10% and 20% based on samples volume. The results presented that the highest compressive strength were founded at 5% of POFA, further it is noted that the inclusion of EPS as a soil subtitution decrease the compressive strength. While, the curing periods have a significance effect on the engineering properties of lightweight materials.